Effect of zinc and iron application on vegetative growth and quality of brinjal cv. Pusa Kranti (Indian Journal of Arid Horticulture, 2025)
A field experiment to study the effect of zinc and iron application on vegetative growth and quality of brinjal cultivar Pusa Kranti was conducted during Dec., 2006 to July, 2008 as main crop and ratoon crop of brinjal at the Department of Horticulture, College of Agriculture, Bikaner. The results revealed that soil application of 40 kg FeSO, before transplanting followed by 40 kg ZnSO, ha as soil application showed increased plantheight, stem girth, number of fruits per plant, fruit weight, fruit width, fruit length and ascorbic acid content in the fruits considerably.
Keywords: Brinjal; micronutrient; nutrition; zinc; iron